Applications of Chemical and Biofertilizers On Yield, and Wheat (Triticum aestivum L.) Quality - Hadi, Tamara Sabah (Nabatia, 2025)
To reduce using conventional fertilizer and enhance wheat cultivation sustainability while recorded high production and quality. The study was performed to investigate the applications of integrated conventional and biofertilizers on yield and bread wheat grain quality. Eco-friendly biofertilizers are an essential component of agriculture sustainability and a promising alternative to conventional nitrogen fertilizers. Impacts of four fertilizer treatments consisted of, i.e., T1 Control recommended 75 kg Nitrogen/fed, T2 50 kg Nitrogen /fed + 10 kg/fed blue-green algae, T3 Azotobacter 10 kg/fed + 50 kg Nitrogen /fed and T4 50 kg N/fed + 10 kg blue-green algae + 10 kg Azotobacter. Randomized Complete Block Design (RCBD) was used with three replications and observed that T4 recorded the early days to 50% heading and early days to maturity compared to T1 Control recommended 75 kg N/fed. Plant height and flag leaf area recorded significant increase values under T4. Number of grains per spike, number of spike/square meter, spike length, 1000-grain weight, and grain yield recorded increases under 450 kg N/fed + 10 Kg blue-green algae + 10 Kg Azotobacter. Crude protein enhanced under plants received 50 Kg N/fed + 10 Kg blue-green algae + 10 Kg Azotobacter in comparison to the control. In conclusion, for sustainable wheat cultivation, the integrated application of biofertilizers and conventional significantly increases wheat yield and enhances grain quality under experimental conditions. Thus, the use of biofertilizer led to a significant increase in soil fertility, yield, and wheat grain quality.